Effect of probiotic chewing gum on caries susceptibility in orthodontic patients: a randomised controlled trial - Bronkhorst, Adele (My University, 2012)
Introduction: Treatment with fixed orthodontic appliances leads to the prolonged accumulation of dental plaque. Patients are at risk because they may develop gingival inflammation and enamel demineralisation during treatment. Several studies suggest that chewing probiotic gum improves the oral microbial ecology. The effect in orthodontic patients has not been reported. Aim: To evaluate the effect of a probiotic chewing gum on saliva flow, plaque and gingival indices and mutans streptococci and lactobacilli in orthodontic patients. Methods: 27 orthodontic patients with fixed appliances completed a double-blind, randomised cross-over study over a period of 16 weeks. The DMFS, sucrose and fiber consumption was assessed. Following a washout period of 28 days either a probiotic gum containing 108 CFU/gum Lactobacillus reuteri ATCC 55730 and PTA 5289 or a placebo were chewed for 10 minutes twice daily for 28 days. Plaque and gingival indices and saliva flow were measured initially and after chewing gum. Saliva was cultured and the number of mutans streptococci and lactobacilli determined. The results were analysed using the Student’s t-test and ANOVA. Results: The placebo gum reduced saliva flow significantly (p=0.032) while this effect was not significant after patients chewed the probiotic gum. There was a decrease in the plaque and gingival indices and salivary microorganisms, and an increase saliva flow in 26% of the patients after they chewed the probiotic gum. Conclusion: Chewing sugar-free probiotic gum may reduce the risk of developing white spot lesions and gingival inflammation in susceptible orthodontic patients.
Keywords: Orthodontics